Analysis of Climate Variability and Agricultural Productivity in Mizoram, Northeast India - Saitluanga, Benjamin L; Lalchhandama, Gabriel; Rinawma, P (Acta Geographica Debrecina Landscape & Environment series, 2021)
Mountainous regions are considered highly vulnerable to the affects of climate change. The extent of change and variability of climatic parameters is still unexamined in many remote mountainous areas. This paper aims in understanding the change in pattern of rainfall and temperature for a period of 30 years in Mizoram. The analysis of time series changing trend in climatic variables is carried out by using Coefficient of Variation (CV), Mann-Kendall (M-K) and Sen’s Slope estimator. The analysis reveals that high variation is observed for both the variables in all the decadal, three decadal and seasonal change. The CV analysis shows that the highest seasonal rainfall variation occurs during winter and the highest seasonal temperature variation occurs during spring. Mann-Kendall test shows a significant change in rainfall with November showing the highest negative trend of rainfall. The temperature trend analysis in the study also reveals drastic change of temperature. An understanding of climatic change, trend and variability helps in predicting for better natural resources from the susceptibility of climate change.